2021
DOI: 10.1111/ijtd.12234
|View full text |Cite
|
Sign up to set email alerts
|

Integrating training and performance management of civil aviation inspectors: A pilot study of the mediating role of competency‐based training

Abstract: Competency-based training (CBT) is gaining popularity as an approach towards creating a highly skilled workforce while reducing the skill gaps faced by industry.Integrated within an organisation's management systems, it can lead to benefits such as increased productivity and strengthened employee engagement. While CBT of aviation industry personnel is well-researched, CBT of civil aviation inspectors is surprisingly under-researched.To better understand the role that CBT plays as a link between organisational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…This allows students to start their careers as a pilot faster, which ultimately reduces training costs for airlines. In addition, MPL allows airlines to obtain more qualified pilots who will be better prepared to work on commercial aircraft (Kjulavkovska et al 2021). MPL can also help airlines meet the increasing need for qualified pilots expected in the future, as stated by Carey et al (2012) • Full Flight Simulator (FFS) -These are the most advanced and realistic simulators designed to replicate the cockpit and systems of a particular aircraft type (Sadovoy et al 2021;Wikander and Dahlstrom 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows students to start their careers as a pilot faster, which ultimately reduces training costs for airlines. In addition, MPL allows airlines to obtain more qualified pilots who will be better prepared to work on commercial aircraft (Kjulavkovska et al 2021). MPL can also help airlines meet the increasing need for qualified pilots expected in the future, as stated by Carey et al (2012) • Full Flight Simulator (FFS) -These are the most advanced and realistic simulators designed to replicate the cockpit and systems of a particular aircraft type (Sadovoy et al 2021;Wikander and Dahlstrom 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the main advantages over other methods are that CBT provides more flexible and efficient training, allows students to be trained regardless of their location, and allows content to be updated at any time. It is a cost-effective and efficient method that can be used in addition to traditional classroom instruction (Kjulavkovska et al 2021). However, one disadvantage of CBT is that it may not provide the same level of hands-on experience as traditional methods, and the effectiveness of learning may depend on the quality of the software and simulation used (ILO 2020).…”
Section: General Characteristics and Global Experience Of Professiona...mentioning
confidence: 99%
“…A review of studies related to employee training and performance management revealed indications of a positive relationship between them (Kjulavkovska et al , 2022). Training and development are factors in human resource practices that positively influence employee performance (Dierdorff et al , 2010).…”
Section: Theoretical Framework and Hypothesis Approachmentioning
confidence: 99%
“…Pilot training is the foundation for commercial aviation in providing professional pilots [12]. Pilot training is also growing along with the growth of global aviation [13].…”
Section: Introductionmentioning
confidence: 99%